RPL-based networks in static and mobile environment: A performance assessment analysis - Hanane Lamaazi; Nabil Benamar; Antonio J. Jara (Journal of King Saud University: Computer and Information Sciences)
The IPv6 Routing Protocol for Low Power and Lossy Networks (RPL) used in the Internet of Things has some shortcoming when the network is dense and with mobile environment. In this paper, we evaluate the performances of RPL in three configurations: network scalability, multiple sink and mobility models. To this end, two different scenarios are implemented using the Cooja simulator. The first one is based on group models. The second scenario is based on the entity mobility models. Our simulation results show that RPL performances are greatly influenced by the number of nodes, the number of sink nodes, and the mobility type. The scalability of the network increases all metrics while providing less packet loss. Additionally, the number of sink nodes directly affects the RPL performances. The energy consumption is reduced in the case of multiple sink nodes by 55.86%, which is less than the case of a single sink. Keywords: RPL routing protocol, ETX, Energy consumption, Mobility models